Chemokines Profiling of Patients with Preterm Birth - Piotr Laudanski; Adam Lemancewicz; Pawel Kuc; Karol Charkiewicz; Barbara Ramotowska; Malgorzata Kretowska; Elwira Jasinska; Grzegorz Raba; Katarzyna Karwasik-Kajszczarek; Janusz Kraczkowski; Tadeusz Laudanski (Hindawi Limited, 2014)
Introduction. Nowadays it is thought that the main cause of premature birth is subclinical infection. However, none of the currently used methods provide effective prevention to preterm labor. The aim of the study was to determine the concentration of selected chemokines in sera of patients with premature birth without clinical signs of infection (n=62), threatened preterm labor (n=47), and term births (n=28). Method. To assess the concentration of chemokines in the blood serum, we used a multiplex method, which allows the simultaneous determination of 40 chemokines per sample. The sets consist of the following chemokines: 6Ckine/CCL21, Axl, BTC, CCL28, CTACK/CCL27, CXCL16, ENA-78/CXCL5, Eotaxin-3/CCL26, GCP-2/CXC, GRO (GROα/CXCL1, GROβ/CXCL2 and GROγ/CXCL3), HCC-1/CCL14, HCC-4/CCL16, IL-9, IL-17F, IL18-BPa, IL-28A, IL-29, IL-31, IP-10/CXCL10, I-TAC/CXCL11, LIF, LIGHT/TNFSF14, Lymphotactin/XCL1, MCP-2/CCL8, MCP-3/CCL7, MCP-4/CCL13, MDC/CCL22, MIF, MIP-3α/CCL20, MIP-3-β/CCL19, MPIF-1/CCL23, NAP-2/CXCL7, MSPα, OPN, PARC/CCL18, PF4, SDF-1/CXCL12, TARC/CCL17, TECK/CCL25, and TSLP. Results. We showed possible implication of 4 chemokines, that is, HCC-4, I-TAC, MIP-3α, and TARC in women with symptoms of preterm delivery. Conclusion. On the basis of our findings, it seems that the chemokines may play role in the pathogenesis of preterm labor. Defining their potential as biochemical markers of preterm birth requires further investigation on larger group of patients.